Implantación de un sistema contable al negocio Aa&r Variedades ubicada en la ciudad de Gualaquiza, provincia de Morona Santiago, correspondiente al periodo 01 de enero al 31 de marzo de 2016. - Peralta Ayora, Mónica Elizabeth (2018)
The main purpose of this thesis is to fulfill one of the requirements established at the National University of Loja prior to choosing the degree of Engineering in accounting and Audit CPA, as well as to provide an optimal accounting system to the local commercial with the purpose of improving its profitability. In order to comply with the objectives set, in the first instance the initial documentation was ordered and classified as purchase and sale invoices, then proceeded to draw up the initial inventory where the rights and obligations with which the business account prior to commencing business. The merchandise account is controlled by the use of kardex cards; This way, an excessive purchase or a shortage of a specific item is avoided. With these data, the Initial Statement is drawn up, with the operation memo, the Daily Book is prepared; with the help of the purchase and sale annexes, subsequent the increase of each of the accounts, the Balance of Verification, Worksheet where they include the respective own adjustments of the operations carried out in the period of investigation and to conclude the presentation of the Financial Statements. At the conclusion of this investigation the annexes or auxiliary of the purchases and sales of merchandise are established, the physical files were ordered fundamental steps to start with the accounting process, at the end of the accounting practice a profit was obtained as the income is higher to the expenses, it is important to mention the control of the merchandise with the use of the cards, with this it avoids that the stock is exhausted or also the unnecessary purchases.